Euglycemic Diabetic Ketoacidosis Related to SGLT2 Inhibitor Use in a Patient With Cobalamin C Deficiency and Diabetes - Camilia Kamoun; Jaclyn Tamaroff; Sanmati Cuddapah; Marc Yudkoff; Shana McCormack; Jessica I. Gold (Annals of Internal Medicine: Clinical Cases)
A 24-year-old woman with cobalamin C deficiency (CblCD), autoimmune thyroiditis, and recently diagnosed diabetes mellitus presented with weight loss, emesis, and abdominal pain. She had been placed on sodium-glucose cotransporter inhibitor (SGLT2i) therapy because of metformin intolerance, with the addition of a dipeptidyl peptidase-4 inhibitor. Biochemical analyses demonstrated severe acidosis, initially attributed to CblC-associated metabolic decompensation. Subsequent evaluation led to the diagnosis of SGLT2i-induced euglycemic diabetic ketoacidosis in a patient with type 1 diabetes mellitus. This case highlights the importance of assessing for insulin deficiency when evaluating acidosis and the management challenges of common diseases in adults with inherited metabolic disorders.